1
$\begingroup$

I'm trying to prove that

$|\cot (x+iy)|^2=\frac{\cos^2x+\sinh^2y}{\sin^2x+\sinh^2y}$

for $x+iy \in \mathbb{C} \setminus \pi\mathbb{Z}$.

I've tried to use the identities $\cos(iy)=\cosh y$ and $\sin(iy)=i\sinh y$, but I obtain

$|\cot (x+iy)|^2=\frac{\cos^2(x) \cosh^2 y+\sin^2(x) \sinh^2y}{\sin^2(x)\cosh^2 y+\cos^2(x)\sinh^2y}$

What did I miss?

$\endgroup$
1
$\begingroup$

You have missed nothing except simplification

Using $\cos^2x+\sin^2x=\cosh^2y-\sinh^2y=1$, eliminate $\cosh y,\sin x$ from the numerator and $\cosh y,\cos x$ from the denominator.

$\cos^2x\cosh^2y+\sin^2x\sinh^2y=\cos^2x(1+\sinh^2y)+(1-\cos^2x)\sinh^2y=\cos^2x+\sinh^2y$

$\sin^2x\cosh^2y+\cos^2x\sinh^2y=\sin^2x(1+\sinh^2y)+(1-\sin^2x)\sinh^2y=\sin^2x+\sinh^2y$

Again, $\cos^2x+\sinh^2y=1-\sin^2x+\cosh^2y-1=\cosh^2y-\sin^2x$

and $\sin^2x+\sinh^2y=1-\cos^2x+\cosh^2y-1=\cosh^2y-\cos^2x$(this is another simplified form)

$\endgroup$
  • $\begingroup$ And $\cos^2(x)\cosh^2y+\sin^2(x)\sinh^2y=\cos^2x(1+\sinh^2y)+(1-\cos^2x)\sinh^2y$ thanks! $\endgroup$ – Fuente Oct 24 '12 at 10:46
  • $\begingroup$ @Fuente, $\cosh^2y=1+\sinh^2y$, please find the updated answer. $\endgroup$ – lab bhattacharjee Oct 24 '12 at 10:48
  • $\begingroup$ I know, it was a typo .) $\endgroup$ – Fuente Oct 24 '12 at 10:50

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.